Speak To Staff Burnout In Medical Secretarial Roles: Strategies For Self-Care And Support Systems. An Update (Journal of Namibian Studies : History Politics Culture, 2022)
This article addresses the pressing issue of staff burnout in medical secretarial roles, offering strategies for self-care and support systems to mitigate its detrimental effects. Burnout among medical secretaries can lead to decreased productivity, increased errors, and turnover, impacting both individual well-being and patient care quality. The paper examines common burnout triggers and emphasizes the importance of self-care practices such as time management, stress reduction, and boundary setting. Additionally, it highlights the role of organizational support systems, including employee assistance programs, flexible work arrangements, and peer support networks.